Australasian genus Crasilogia Warren (Lepidoptera: Geometridae: Larentiinae) - Schmidt, Olga (Zootaxa, 2020)
The Australasian genus Crasilogia Warren comprising the species C. dispar Warren, C. flavipennis Warren, C. fulvitincta Joicey & Talbo, C. fumipennis Warren, C. gressitti Holloway, C. simplex (Prout), C. parasimplex, sp. nov., and C. diversisimplex, sp. nov. is reviewed based on the museum specimens, including primary types. Lectotype is designated for C. simplex.